Metallurgical process engineering - Yin, Ruiyu; SpringerLink (Online service). (Beijing Metallurgical Industry Press Heidelberg Springer, 2011)
"Metallurgical Process Engineering" discusses large-scale integrated theory on the level of manufacturing production processes, putting forward concepts for exploring non-equilibrium and irreversible complex system. It emphasizes the dynamic and orderly operation of the steel plant manufacturing process, the major elements of which are the flow, process network and program. The book aims at establishing a quasi-continuous and continuous process system for improving several techno-economic indices, minimizing dissipation and enhancing the market competitiveness and sustainability of steel plants. The book is intended for engineers, researchers and managers in the fields of metallurgical engineering, industrial design, and process engineering. Prof. Ruiyu Yin is honorary president of the Central Iron and Steel Research Institute, China, and a member of the Chinese Academy of Engineering.
The "material of choice" - steel -- Uprising of China?s steel industry -- Process manufacturing industry and process engineering -- Engineering science in steel manufacturing process -- Analysis and integration of metallurgical manufacturing process -- Multi-dimensional mass flow control for metallurgical manufacturing process -- Time factors in steel manufacturing process.-Operating dynamics in the production process of steel plant -- Structure and mode of steel plant -- Steel plant and environment.
Electronic reproduction.
Keywords: Metallurgy; Manufacturing processes; Metal trade; Metallurgical plants -- Management; Electronic books